Ksiądz Ludwik Mucha (1904-1962). Kapelan "Hubala", kapłan czasu trudnych wyborów = Father Ludwik Mucha (1904-1962). "Hubal"s chaplain, the priest of the times of hard choices - Karp, Paweł; Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is dedicated to the chaplain of the legendary major "Hubal" as well as a few other partisan units in the years 1940-1945, who later became one of the first Polish chaplains that moved to the Western Recovered Lands. In the post-war Polish reality, he seemed, however, a confused person. Ludwik Mucha received his holy orders in France, where he worked actively to help the Polish community.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia